2009
DOI: 10.1083/jcb.200903152
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelin synthase-related protein SMSr controls ceramide homeostasis in the ER

Abstract: Ceramides are central intermediates of sphingolipid metabolism with critical functions in cell organization and survival. They are synthesized on the cytosolic surface of the endoplasmic reticulum (ER) and transported by ceramide transfer protein to the Golgi for conversion to sphingomyelin (SM) by SM synthase SMS1. In this study, we report the identification of an SMS1-related (SMSr) enzyme, which catalyses the synthesis of the SM analogue ceramide phosphoethanolamine (CPE) in the ER lumen. Strikingly, SMSr p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
215
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(230 citation statements)
references
References 46 publications
(84 reference statements)
15
215
0
Order By: Relevance
“…1, A-C). However, it is clear that depletion of SMSr elevates steady-state levels of ceramide (12). We conclude that the major site of SMSr regulation of ceramide is not at the level of biosynthesis, but rather by regulating one or more of the upstream metabolic processes that determine ceramide levels.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…1, A-C). However, it is clear that depletion of SMSr elevates steady-state levels of ceramide (12). We conclude that the major site of SMSr regulation of ceramide is not at the level of biosynthesis, but rather by regulating one or more of the upstream metabolic processes that determine ceramide levels.…”
Section: Resultsmentioning
confidence: 72%
“…However, the mechanism by which the ORMDL proteins regulate ceramide levels and whether they are responsive to changes in cellular ceramide content have not been established. Mammalian cells also express a member of the sphingomyelin synthase family, SMSr, which has been implicated as a ceramide sensor in ceramide homeostasis (12). SMSr generates phosphoethanolamine-ceramide rather than sphingomyelin, is a low efficiency enzyme and, unlike the conventional sphingomyelin synthases, is localized in the endoplasmic reticulum rather than in the Golgi apparatus.…”
mentioning
confidence: 99%
“…58 Indeed, we recently demonstrated that Drosophila and human SMSr proteins catalyze EPC biosynthesis and, contrary to SMS1 and SMS2, localize to the ER. 69 SMSr thus qualifies as the ER-resident CPE synthase originally described by Malgat et al 41,42 Remarkably, we have recently found that SMSr produces only trace amounts of CPE and that bulk production of CPE in Drosophila S2 cells requires a different enzyme. This second, insect-specific CPE synthase uses CDP-ethanolamine instead of PE as headgroup donor, 69 analogous to the ethanolaminephosphotransferases of the Kennedy pathway.…”
Section: Sms Family Members Display Striking Variations In Substrate mentioning
confidence: 69%
“…69 SMSr thus qualifies as the ER-resident CPE synthase originally described by Malgat et al 41,42 Remarkably, we have recently found that SMSr produces only trace amounts of CPE and that bulk production of CPE in Drosophila S2 cells requires a different enzyme. This second, insect-specific CPE synthase uses CDP-ethanolamine instead of PE as headgroup donor, 69 analogous to the ethanolaminephosphotransferases of the Kennedy pathway. 70 This implies that, contrary to SM synthesis in mammals, bulk production of CPE in insects occurs in the cytosolic leaflet of the membrane.…”
Section: Sms Family Members Display Striking Variations In Substrate mentioning
confidence: 69%
“…This ER-localized protein, SMSr is homologous to SM synthase but lacks SM synthase activity, having instead a weak ability to generate ceramide-phosphoethanolamine (CPE). Surprisingly, knockdown of SMSr causes a dramatic increase in ceramide levels that cannot be explained by a block in CPE production (Vacaru et al 2009). Rather, SMSr may act as a sensor that detects ER ceramides and down-regulates ceramide production.…”
Section: Sphingolipid Homeostasis In the Er And Beyondmentioning
confidence: 99%